2015
DOI: 10.1155/2015/468917
|View full text |Cite
|
Sign up to set email alerts
|

Development of a New Binary Solvent System Using Ionic Liquids as Additives to Improve Rotenone Extraction Yield from MalaysiaDerrissp.

Abstract: Rotenone is one of the prominent insecticidal isoflavonoid compounds which can be isolated from the extract ofDerrissp. plant. Despite being an effective compound in exterminating pests in a minute concentration, procuring a significant amount of rotenone in the extracts for commercialized biopesticides purposes is a challenge to be attained. Therefore, the objective of this study was to determine the best ionic liquid (IL) which gives the highest yield of rotenone. The normal soaking extraction (NSE) method w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…However, most studies prefer a binary solvent system as compared to the mono-solvent system to extract bioactive compounds ( Othman et al, 2015 , Thoo et al, 2010 , Wong et al, 2014 ). A binary solvent system (or known as bi-solvent system) is defined as a combination of two solvents (ionic liquids and/or organic solvents) with regard to their relative polarity ( Othman et al, 2015 ). A study by Othman et al (2015) had proved the binary solvent system’s potential to increase the yield of targeted compounds of any herbal medicinal plants.…”
Section: Solvent Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most studies prefer a binary solvent system as compared to the mono-solvent system to extract bioactive compounds ( Othman et al, 2015 , Thoo et al, 2010 , Wong et al, 2014 ). A binary solvent system (or known as bi-solvent system) is defined as a combination of two solvents (ionic liquids and/or organic solvents) with regard to their relative polarity ( Othman et al, 2015 ). A study by Othman et al (2015) had proved the binary solvent system’s potential to increase the yield of targeted compounds of any herbal medicinal plants.…”
Section: Solvent Systemmentioning
confidence: 99%
“…A binary solvent system (or known as bi-solvent system) is defined as a combination of two solvents (ionic liquids and/or organic solvents) with regard to their relative polarity ( Othman et al, 2015 ). A study by Othman et al (2015) had proved the binary solvent system’s potential to increase the yield of targeted compounds of any herbal medicinal plants. The results given by 1-butyl-3-methylimidazolium trifluoromethanesulfonate (OTf) combined with acetone had the highest rotenone content as compared to other binary solvents and control (acetone).…”
Section: Solvent Systemmentioning
confidence: 99%
“…Previous study has shown that DESs which are comprised of choline chloride and 1,4-butanediol with a ratio of 1 : 5 produced the highest yield of extracted flavonoids (myricetin and amentoflavone) [6]. In addition, a preliminary study on comparing the efficiency between ionic liquid (IL), acetone, and alcohol-based deep eutectic binary solvent system in extracting rotenone compound also showed a remarkable potential of alcohol-based deep eutectic binary solvent system (Figure 1(b)) to be used as a green additive in extraction of rotenone (isoflavonoid) [5]. A study conducted by Zubairi et al [7,8] on the optimal condition for rotenone extraction which was comprised of solvent types, solvent-to-solid ratio, and particle size recorded acetone as the best solvent for extraction with optimal solvent-to-solid ratio of 10 ml/g and 0.84 mm particle size.…”
Section: Introductionmentioning
confidence: 95%
“…Thus, alternative green solvent with high extraction efficiency is crucial in enhancing the quality and quantity of rotenone extract. In the case of rotenone (Figure 1(a)) extraction, the previous study showed the potential of environmental friendly ionic liquid binary solvent system to increase the yield of rotenone extracted compared to organic solvent (acetone) [5]. However, in terms of costing and convenience, ionic liquid is expensive, hygroscopic, and hard to handle, limiting its usage as an extraction medium.…”
Section: Introductionmentioning
confidence: 99%
“…The best extraction time was between 800 and 840 min with a yield of rotenone of 830 mg to 890 mg, respectively, and a rotenone concentration of 2800 to 2950 ppm. Othman et al . studied the best ionic liquid method to obtain the highest yield of rotenone from Derris .…”
Section: Introductionmentioning
confidence: 99%